EUS-Guided Antegrade Transhepatic Placement of a Self-Expandable Metal Stent in Hepatico-Jejunal Anastomosis - Artifon, Everson L A; Safatle-Ribeiro, Adriana Vaz; Ferreira, Flávio Coelho; Poli-de-Figueiredo, Luiz; Rasslan, Samir; Carnevale, Francisco; Otoch, José Pinhata; Sakai, Paulo; Kahaleh, Michel (JOP. Journal of the Pancreas, 2011)
<!–[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Context To demonstrate an EUS-guided biliary drainage in patient with gastrointestinal tract modified surgically. Case report An EUS guided access to the left intra hepatic duct, followed by an antegrade passage of a partially self-expandable metal stent that was removed by using an enteroscope, in one patient with hepatico-jejunal anastomosis. There were no early or delayed complications and the procedure was effective in relieving jaundice until the self-expandable metal stent was removed, 3 months later. A cholangiogram was obtained via enteroscopy, after removal of self-expandable metal stent, and found to be normal. The patient had an uneventful evaluation afterwards. Conclusion The indication of these procedures must be made under a multidisciplinary view while sharing information with the patient or legal guardian. EUS-guided biliary drainage is feasible when performed by professionals with expertise in biliopancreatic endoscopy and advanced echo-endoscopy and should be performed currently under rigorous protocol in educational institutions.